A brief history of finance in China - Zhengping, Chen (Economic history in China series., 2014)
This is a short history of finance in China, covering the development of native financial institutions and practices, the influx of foreign banks, the financial policies of governments in modern China, and the beginnings of the Chinese Communist Party financial system. The book provides a good overview of this topic, and will be of interest to those who realize that the business culture in China has a lot to do with the history of financial institutions and foreign capital in the country. A Brief History of Finance in China is also helpful in the way that it discusses Chinese traditions, not just the country's modern finances. (Series: Economic History in China).